2004
DOI: 10.1080/09687860400003941
|View full text |Cite
|
Sign up to set email alerts
|

Purification and properties of theEscherichia colinucleoside transporter NupG, a paradigm for a major facilitator transporter sub-family

Abstract: NupG from Escherichia coli is the archetype of a family of nucleoside transporters found in several eubacterial groups and has distant homologues in eukaryotes, including man. To facilitate investigation of its molecular mechanism, we developed methods for expressing an oligohistidine-tagged form of NupG both at high levels (>20% of the inner membrane protein) in E. coli and in Xenopus laevis oocytes. In E. coli recombinant NupG transported purine (adenosine) and pyrimidine (uridine) nucleosides with apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 39 publications
6
46
1
Order By: Relevance
“…Expression of this nucleoside transporter in N. parisii (ERTm1) (NEPG_00699) can be detected throughout infection (Supplemental Table S5). This symporter is homologous to the Escherichia coli gene NupG, a broad-specificity transporter of purine and pyrimidine nucleosides that uses the proton motive force to drive nucleoside transport (Xie et al 2004). Evolutionarily unrelated equilibrative nucleoside transporters are used by eukaryotic parasites such as Trypanosoma species, which, like microsporidia, lack complete nucleoside synthesis pathways and need to import nucleosides from their hosts (Sanchez et al 2002).…”
Section: Phylogenomics Of the Microsporidia And Nematocidamentioning
confidence: 99%
“…Expression of this nucleoside transporter in N. parisii (ERTm1) (NEPG_00699) can be detected throughout infection (Supplemental Table S5). This symporter is homologous to the Escherichia coli gene NupG, a broad-specificity transporter of purine and pyrimidine nucleosides that uses the proton motive force to drive nucleoside transport (Xie et al 2004). Evolutionarily unrelated equilibrative nucleoside transporters are used by eukaryotic parasites such as Trypanosoma species, which, like microsporidia, lack complete nucleoside synthesis pathways and need to import nucleosides from their hosts (Sanchez et al 2002).…”
Section: Phylogenomics Of the Microsporidia And Nematocidamentioning
confidence: 99%
“…However, it did confer modest resistance to arsenate, and the quenching of its intrinsic fluorescence by arsenate but not arsenite is consistent with a putative role as an arsenate transporter. The relatively low apparent affinity of the transporter for arsenate probably reflects measurement of binding under non-energized conditions, as has been observed for several other bacterial proton-dependent transporters [12]. Phylogenetic analysis of currently known ACR3 family members showed that these can be grouped into five subfamilies.…”
Section: Discussionmentioning
confidence: 94%
“…For Fourier transform infrared (FTIR) spectroscopy, purified protein was concentrated to 1.0 mg/ml using a centrifugal membrane-concentrating device with a molecular weight cut-off of 50,000 (Sartorius Stedim UK Ltd). Measurements were then made using a using a Nicolet 560 FT-IR spectrometer essentially as previously described [12].…”
Section: Spectroscopymentioning
confidence: 99%
“…Complex formation and light activation have been investigated with sensory rhodopsin II and its transducer in nativelike membranes ) and the conformation of a 7-TM sensory rhodopsin in lipids has been characterized (Shi et al 2011). Solid-state NMR can also be used to investigate the specificity and properties of ligand binding to wild-type and mutant forms of membrane proteins (Patching et al 2004a, Xie et al 2004, including the measurement of binding constants and rate constants for dissociation with weakly-binding (mM-mM affinity) ligands (Patching et al 2004b). All of this type of information can be combined with structures from crystallography and/or solution-state NMR to understand better how native ligands or drug molecules interact with membrane proteins and can be used to assist the design of new treatments for human disease.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%